AN IMPERIAL SYLLABUS. Issue 2 (May 2016) - Garrett, Matthew
ABSTRACT: Ten Books That Shaped the British Empire, edited by distinguished historians Antoinette Burton and Isabel Hofmeyr, brings together ten essays on individual books with a substantial methodological introduction. Covering the full geographical expanse of the Empire, the volume seeks to unify book and imperial history through careful accounts of the circulation, recycling, and uptake of each of the books under consideration. The upshot is an invaluable overall work with important individual contributions. At the same time, the project's methodology and mode of presentation raise questions for the writing of history, particularly at the nexus of the histories of empire and of the book, that are reiterated but never queried within the volume itself. Specifically, in its focus on the moment of the circulation of texts, Ten Books That Shaped the British Empire reflects a general condition in the human sciences: a resistance to narrative, to causality, and to critique, which this essay attempts to describe and briefly explain.